If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(y + 3) + y = 5Y + 12 Reorder the terms: 4(3 + y) + y = 5Y + 12 (3 * 4 + y * 4) + y = 5Y + 12 (12 + 4y) + y = 5Y + 12 Combine like terms: 4y + y = 5y 12 + 5y = 5Y + 12 Reorder the terms: 12 + 5y = 12 + 5Y Add '-12' to each side of the equation. 12 + -12 + 5y = 12 + -12 + 5Y Combine like terms: 12 + -12 = 0 0 + 5y = 12 + -12 + 5Y 5y = 12 + -12 + 5Y Combine like terms: 12 + -12 = 0 5y = 0 + 5Y 5y = 5Y Solving 5y = 5Y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = Y Simplifying y = Y
| 2/5x-16 | | 4x-y^2=0 | | 4(5x-3)=-8x | | -3x+1=18 | | 25/35=Q10/k | | -5(1-3b)=10b+11(b-7) | | f(x)=x(x+3)-14 | | ln(4x/y3) | | 33=7(2p-1) | | 8n+7=2(4n+3) | | X/4-9/X=0 | | 7m^2-14m-61=-5 | | 5x=-7x+8 | | 1.8e=9 | | n+n+1+n+2=129 | | 2=0.6(2x+4)-0.75(4x-5) | | 2y+5=2(y+2)+1 | | 12k-15+15=54 | | -6x+3+3x=-7x-9 | | -y^2-y^2= | | -16x=33 | | 7m-3m-6=2m+12 | | 7/15÷3/4 | | 88-11=3x+9x-x | | 9z-4=2z+10 | | 8=x/-5 | | 7.25x=19.125+x | | 5m=6m+56 | | f(x+1)=8x^2+3x | | 5(3+x)= | | 1-5(x+6)=20+2x | | 7d-d-6d+7=4d |